RESEARCH OF THE RHYTHMICAL ABILITIES OF RHYTHMIC GYMNASTS - Giurka Gantcheva; Emil Videv; Bisser Grigorov (Scientific Publishing House. NSA Press, 2018)
Rhythmical abilities, being part of the coordination abilities of athletes, are an important factor for the successful realization in the complex-coordination kinds of sports. The initial learning of the exercises requires the strict following of a rhythm, set with music, to distinguish the different phases of motor activities and their duration. The rhythm of motor activities is subjected to the inner rhythm of the performer, to the different rhythm of the movements with the apparatuses, and to the rhythmical structure of the music accompaniment. The rhythmical execution and the harmonious connection between movements and music is one of the major characteristics of gymnastics events. The aim of the research is to study the rhythmical abilities of athletes, practicing kinds of sports whose motor activity requires the use of musical accompaniment and those which do not require such. The research was done among 72 individuals. Methods: For coordination in rhythm we used four tests: Frontal kicking with legs and arms on the wall - (Fkla), Jumps in four squares - (J4sq), Crossover jumps in four squares - (Cj4sq), Kicking with legs and arms - (Kla). The results from the tests - Jumps in four squares и Crossover jumps in four squares - correlate with each other significantly with the gymnasts (.710**) and moderately with the athletes practicing other kinds of sports (.358**). The results from the agility tests correlate significantly with the gymnasts (.723**), and moderately with the athletes from the other sports (.654**). The mean values (х=10.20, х=4.41) and (х=10.6, х=8.24) of the tests, performed with arms and legs are better with the gymnasts. The results from the research showed the necessity of adapting the applied tests so that they could be implemented in research with different age groups.